Composition of stable carbon and nitrogen isotopes in five wetland plants and sediments from the Pearl River estuary, South China. Issue 7 (8th August 2016) - Miao, S. Y.; Long, L. D.; Tao, W. Q.; Zeng, Q. C.; Chen, J. H.; Huang, J. L.; Wu, Q. H.; Tang, Y.J.
ABSTRACT: This study sampled five plant species and adjoining sediments from the Qi'ao (Zhuhai) and Nansha (Guangzhou) coastal wetlands located in the Pearl River estuary, South China. The compositions of stable carbon and nitrogen isotopes as well as the content of carbon and nitrogen in the samples were analysed. Differences in carbon/nitrogen (C/N) ratio, and habitat feature were compared between exotic plants ( Spartina alterniflora, Sonneratia apetala, and Laguncularia racemosa ) and native mangroves ( Aegiceras corniculatum and Acrostichum aureum ). The results showed that for Qi'ao, which is nearer the sea, the conductivity of the sediments at this location was approximately two times higher than that at Nansha (more inland). The composition of both δ 13 C and δ 15 N in sediments was also higher at Qi'ao (−26.52‰ to −23.83‰ and 6.25‰ to 11.53‰, respectively) as compared to Nansha (−29.30‰ to −27.43‰ and 3.34‰ to 4.73‰, respectively). Overall, the exotic plants S. alterniflora and S. apetala at Qi'ao and S. apetala and L. racemosa at Nansha had an average δ 15 N composition significantly higher than that of the native plants A. corniculatum and A. aureum . This suggests that the three exotic plants employ a different mechanism of δ 15 N storage and utilisation as compared to the two native mangrove species, which may result in changes in ecological and biogeochemical processes in these coast wetlands.